Characteristics, pathogenic and therapeutic role of gut microbiota in immunoglobulin A nephropathy - Yao, Kaijin; Zheng, Lingqian; Chen, Wenmin; Xie, Yina; Liao, Chunling; Zhou, Tianbiao (Frontiers in Immunology, 2025)
Immunoglobulin A nephropathy (IgAN) is the most prevalent glomerulonephritis in the world, and it is one of the leading causes of end-stage kidney disease. It is now believed that the pathogenesis of IgAN is the mesangial deposition of immune complex containing galactose-deficient IgA1, resulting in glomerular injury. Current treatments for IgAN include supportive care and immunosuppressive therapy. A growing number of studies found that the gut microbiota in IgAN was dysregulated. Gut microbiota may be involved in the development and progression of IgAN through three main aspects: destruction of intestinal barrier, changes in metabolites and abnormal mucosal immunity. Interestingly, therapies by modulating the gut microbiota, such as fecal microbiota transplantation, antibiotic treatment, probiotic treatment, Chinese herbal medicine Zhen Wu Tang treatment, gluten-free diet, and hydroxychloroquine treatment, can improve IgAN. In this review, the alteration of gut microbiota in IgAN, potential pathogenic roles of gut microbiota on IgAN and potential approaches to treat IgAN by modulating the gut microbiota are summarized.